Human immunodeficiency viru s infection possibly acquired by traumatic inhalation of cocaine - Tavares, Walter (Brazilian Journal of Sexually Transmitted Diseases, 1999)
The author presents two heterosexual male patients HIV infected, who re ferred cocaine addiction by inhalation. Patients usually practiced the inhalation by means of a tube that was used by other members of the group. This instrument sometimes was polluted by blood from a nasal mucous membrane trauma of preceded addicted persons. The author argues the possibility of acquiring HIV infection by traumatic inhalation of cocaine.